The Adequacy of Disclosure of Related Party Transactions - Saber Sheri; Elham Amiri (Allameh Tabataba'i University Press, 2011)

(untitled) (مطالعات تجربی حسابداری مالی)
In Recent corporate scandals, one of the recurring areas of concern is related party transactions. Concern about related party transactions has increased as a result of at least two high profile bankruptcies: Enron and Adelphia. The key reason of their collapse has been attributable at least in part to extensive purposefully use of undisclosed or “under-disclosed” transactions. In this research, the adequacy of disclosure of related party transactions is investigated by means of a checklist prepared according to Iranian accounting standard No.12. Research is performed over the years of 2006 to 2010 among Tehran stock exchange listed companies. According to accounting standard No.12, 14 disclosure requirements are set out and divided into two groups: 5 items are classified as general disclosure items and others are classified as other disclosure items. Then, mean disclosure is calculated and compared with the 50-percent level of disclosure included in Doing Business Reports. The results show that companies disclose 46 percent of general disclosure items and 58 percent to 62 percent of other disclosure items. Finally, the disclosure level of each disclosure requirement is determined. The results suggest deficiency in compliance with accounting standard No.12.